(untitled) (Actualizaciones en Sida e Infectología, 2023)
Background: Dual therapy has emerged as a novel concept for HIV treatment. Thisstudy was aimed at comparing a nucleoside-sparing dual regimen consisting of ATV/r + RAL (DT) vs standard therapy of ATV/r + TDF/FTC (TT) among individuals failing first NNRTI-containing treatment. Methods: Randomized multicenter open-label pilot study. Primary outcome: proportion of subjects with plasma HIV-1 RNA below the limit of detection (<50 copies/mL) at 48 weeks (W48). Secondary outcomes: proportion of discontinuation due to adverse events (AEs), time until viral suppression, time until loss of virological response, development of integrase resistance mutations, and absolute change in CD4 counts. The primary outcome was analyzed using the FDA snapshot analysis. Results: Out of 57 participants screened, 34 were randomized to receive: DT (n: 18) or TT (n: 16). At W48, virological response was achieved in 67% (n: 12/18) of participants receiving DT and 88% (n: 14/16) receiving TT by FDA snapshot analysis (p = NS) and 73% and 93% by per-protocol analysis (p = NS). CD4 cell count median change from baseline to W48 was +119 and + 52 cell/μL in DT and TT, respectively. Four participants receiving DT and one TT presented virological failure at W48, with low pVL. One participant developed an integrase resistance mutation (155H) and suppressed later on TT. Conclusion: ATV/r+RAL as second-line therapy showed a trend to more frequent virological failure, compared to TT, although the study was unpowered to prove this difference. No major differences were seen in tolerance or toxicity. This study is registered with ClinicalTrials.gov, Number: NCT01829802